Kebijakan dan Implementasi Otonomi Khusus di Papua Barat Daya - Sinen, Karmila (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study investigates the policy and implementation of special autonomy in West Papua Daya Province, a newly established province resulting from the division of West Papua Province. The research analyzes the prevailing special autonomy policy, examines its on-the-ground implementation, and evaluates its impact on the region's social, economic, and cultural development. Employing a qualitative methodology with a case study approach, data were collected through in-depth interviews with key stakeholders, participatory observation, and document analysis. The findings illuminate several challenges and opportunities inherent in the implementation of special autonomy in West Papua Daya Province, and offer policy recommendations aimed at improving the effectiveness and long-term sustainability of the special autonomy program.